2010
DOI: 10.1111/j.1365-2427.2009.02378.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple stressors in north temperate streams: lessons from linked forest–stream ecosystems in northern Japan

Abstract: SUMMARY1. Streams are highly connected to their landscapes and so are easily altered by multiple stressors that affect both uplands and riparian zones, and the streams themselves. These include dams and diversions, channelisation, deforestation, water pollution, biological invasions and climate change. 2. We review research conducted in Hokkaido Island, northern Japan, which measured the effects of many of these stressors on both stream food webs and fluxes of invertebrates to and from the riparian zone that f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 84 publications
(234 reference statements)
0
54
1
2
Order By: Relevance
“…The importance of effects due to stressor interactions, however, may be lessened when individual stressors have large effects [185]. In Hokkaido (Japan) streams, extensive experimentation of deforestation, channelization, erosion-control dams, biological invasions, and climate change revealed that most of these stressors caused 30 to 90% declines in foraging, growth, or abundance of aquatic or terrestrial predators [184].…”
Section: Stressor Interactions and Stressor Dominancementioning
confidence: 99%
See 2 more Smart Citations
“…The importance of effects due to stressor interactions, however, may be lessened when individual stressors have large effects [185]. In Hokkaido (Japan) streams, extensive experimentation of deforestation, channelization, erosion-control dams, biological invasions, and climate change revealed that most of these stressors caused 30 to 90% declines in foraging, growth, or abundance of aquatic or terrestrial predators [184].…”
Section: Stressor Interactions and Stressor Dominancementioning
confidence: 99%
“…The question of which organism or community is the most appropriate test species will exist in any human-dominated ecosystem when attempting to rank the relative importance of the existing stressors. We therefore reiterate the call for a more prescriptive, experimental approach to establishing stressor importance that links controlled laboratory studies with field-based ecological manipulations and studies of exposure and response relationships between key physical, biological, and chemical conditions [14,24,181,185,[196][197][198].…”
Section: Stressor Interactions and Stressor Dominancementioning
confidence: 99%
See 1 more Smart Citation
“…These experiences have forged new friendships and connections that span the globe (Fig. 6) and continue to foster reciprocal collaborations and new research and synthesis among Japanese researchers and western scientists that are advancing ecological research worldwide (e.g., Dunham et al 2008;Fausch et al 2010;Richardson and Sato 2015;Sato et al 2016).…”
Section: Conclusion: An Enduring Legacy For Ecologymentioning
confidence: 99%
“…These emergences can form a substantial part of benthic production and are of importance to riparian consumers such as birds, bats, lizards and spiders, and contribute 25-100% of the energy or carbon to such species (e.g. Fausch et al 2010). …”
Section: Landscape Level: Terrestrial Vs Aquatic Ecosystemsmentioning
confidence: 99%